"To Make It Belong to Who I Was, to Who I Became": Atom Egoyan's Ararat and Symbiogenesis among the Diaspora of the Armenian Genocide. Issue 1 (2nd January 2022) - Woolford, Andrew
ABSTRACT: In Canadian-Armenian director Atom Egoyan's film about the Armenian genocide, Mount Ararat is more than a symbol; as the titular character, it assumes a dynamic role. Indeed, Mount Ararat has historically played a co-constitutive part in the production of Armenian identity. The Armenian genocide threatened to sever symbiogenesis, the process of becoming together, between the mountain and its people. This symbiogenesis is captured in Ararat, which shows members of the diaspora grappling with the difficulty of accessing the sacred mountain, as well as lost territories in western Armenia/eastern Turkey, conveying what this deterritorialization means to their lives as displaced Armenians living in Canada. Through his representation of the contested landscape around Mount Ararat, Egoyan demonstrates that attending to this symbiogenetic relationship has significant implications for thinking through questions of diaspora identity, redress, and truth in the aftermath of the Armenian genocide.